DEVELOPMENT OF A PRELIMINARY PROCESSING MODULE FOR THE SPECTRAL INDEX EVI BASED ON MULTISPECTRAL DATA - Seitnazarov, Kuanyshbay Kenesbaevich; Madirimova, Saodatjon Madirimovna; Turemuratova, Biybinaz Kenesbaevna; Aitmuratov, Bakhtiyar Bakhbergenovich (SCIENCE and SOCIETY, 2026)
This article examines the development and implementation of a preprocessing module for multispectral satellite imagery as part of a software system intended for use within an expert system for Earth remote sensing data analysis. The proposed module provides a complete transformation pipeline for raw input data. Particular attention is paid to the calculation of the Enhanced Vegetation Index (EVI), which demonstrates high sensitivity to vegetation condition, especially chlorophyll content. It should also be noted that the module architecture is based on a pipeline approach, ensuring modularity, scalability, and robustness in the processing of large volumes of satellite imagery. The implementation includes computational optimization as well as integration with a geospatial PostgreSQL/PostGIS database.